2020
DOI: 10.1007/s13365-020-00884-7
|View full text |Cite
|
Sign up to set email alerts
|

Severe rapidly progressive Guillain-Barré syndrome in the setting of acute COVID-19 disease

Abstract: There is concern that the global burden of coronavirus disease of 2019 (COVID-19) due to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection might yield an increased occurrence of Guillain-Barré syndrome (GBS). It is currently unknown whether concomitant SARS-CoV-2 infection and GBS are pathophysiologically related, what biomarkers are useful for diagnosis, and what is the optimal treatment given the medical comorbidities, complications, and simultaneous infection. We report a patient who de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 16 publications
2
48
0
1
Order By: Relevance
“…Although the CSF RBC count was only reported for 61/430 (14%) patients [ 22 , 28 , 29 , 31 , 35 , 39 , 40 , 44 , 73 , 74 , 77 , 78 , 81 , 89 , 92 , 102 , 110 , 118 , [120] , [121] , [122] , [123] , 128 , 133 , 134 , [138] , [139] , [140] , 156 , 165 , 166 , [172] , [173] , [174] , [175] , [176] , 180 , 184 , 188 , 191 , 192 , 198 , 202 , 204 , 208 , 215 , 220 , 225 , 227 , 233 , 241 , 242 , 246 ], the CSF white blood cell (WBC) count was provided for 409/430 (95%) patients, 270 (66%) of whom had >0 cells/μL, >1 WBC:1,000 RBC or were noted to have “pleocytosis” ( Fig. 3 ) [ [5] , [6] , [7] , [8] , 10 , 13 , [15] , [16] , [17] , [18] ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the CSF RBC count was only reported for 61/430 (14%) patients [ 22 , 28 , 29 , 31 , 35 , 39 , 40 , 44 , 73 , 74 , 77 , 78 , 81 , 89 , 92 , 102 , 110 , 118 , [120] , [121] , [122] , [123] , 128 , 133 , 134 , [138] , [139] , [140] , 156 , 165 , 166 , [172] , [173] , [174] , [175] , [176] , 180 , 184 , 188 , 191 , 192 , 198 , 202 , 204 , 208 , 215 , 220 , 225 , 227 , 233 , 241 , 242 , 246 ], the CSF white blood cell (WBC) count was provided for 409/430 (95%) patients, 270 (66%) of whom had >0 cells/μL, >1 WBC:1,000 RBC or were noted to have “pleocytosis” ( Fig. 3 ) [ [5] , [6] , [7] , [8] , 10 , 13 , [15] , [16] , [17] , [18] ...…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Demirci Otluoglu et al noted CSF protein was 0.4 mg/L (0.04 mg/dL) and Dharsandiya et al indicated the CSF protein was 39 g/dL (3,900 mg/dL), but both authors described the protein as normal, and Matos et al reported a CSF protein of 0.78 mg/dL, but noted it was mildly elevated; we presumed these were meant to be 0.4g/L (40 mg/dL), 39 mg/dL, and 78 mg/dL, respectively [ 150 , 151 , 200 ]. There were 27/397 (7%) patients who had CSF protein >200 mg/dL (19/27 (70%) with symptoms that localized to the CNS and 8/27 (30%) with symptoms that localized to the PNS) [ 16 , 21 , 31 , 32 , 34 , 44 , 53 , 58 , 78 , 81 , 89 , 104 , 113 , 127 , 128 , 160 , 170 , 173 , 176 , 184 , 199 , [220] , [221] , [222] , 245 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed all the cases excluded by Abu-Rumeileh et al also and found no positive ganglioside antibodies among those excluded patients. We have identified seven more reported individual cases, which have not been included in any case review to date [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Including our current case, there are 83 individual cases of COVID-19 related GBS or MFS being reported to date.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…Overall, we identified 51 COVID-19-associated GBS cases which we included in this study. However, among these patients, there were five (5) cases who met the GBS symptom criteria, but did not have documentation of nerve conduction study results [9,47,50,52]; as we could not conclude whether they involved demyelination or axonal neuropathy, these cases were not included in the classification of GBS subtypes.…”
Section: Demographic and Clinical Characteristics Of The Covid-19-assmentioning
confidence: 99%